PENGGUNAAN METODE PEMETAAN PIKIRAN (MIND MAPPING) UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA PADA ANAK TK LAKSHMI 7 SURAKARTA - Kusumaningtyas, Lydia Ersta (UNIVERSITAS SLAMET RIYADI, 2015)
This research aims at knowing the use of mind maping method to improve the languagecompetence of kindergarthen students in TK Lakshmi 7 Turisari Surakarta 2014/2015. Thesubject of this research is 29 pupils; 13 boys and 16 girls.The data collecting technique applied is observation, interview and documentation.Tnis research is an action research with two cycles.Based on the research in cycle one and two, it is proved that mind maping method canimprove the language competence. This method is also proved to be effective.